Use of aripiprazole in an obsessive compulsive disorder case with associated motor tics - A. Alvarado Dafonte; M. Valverde Barea; M. Solis (European Psychiatry, 2022)
Introduction Obsessive compulsive disorder (OCD) is a pathology represented by thoughts, images, impulses or feelings that generate great anxiety and discomfort, as well as the development of compulsive acts and rituals that cause great dysfunction. The comorbidity of different psychiatric disorders with OCD is known, such as impulse control disorder and tic disorder.